PENGARUH MOTIVASI, KOMPENSASI, DAN KONFLIK KERJA TERHADAP KINERJA KARYAWAN PADA PT. DEVELOPMENT LEADERSHIP CORPORATION DI DENPASAR - Desak Putu Eka Citra Dewi; I Gusti Ayu Imbayani; Pande Ketut Ribek (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
The purpose of this study was to determine the effect of motivation, compensation and work conflict on employee performance. This research was conducted at PT Development Leadership Corporation in Denpasar. This study uses multiple linear regression analysis to see motivation, compensation, and work conflict on the performance of employees of PT Development Leadership Corporation in Denpasar. The population used is all employees of PT Development Leadership Corporation in Denpasar. The total number of employees is 34 respondents. The data were collected by means of a questionnaire and the sampling method used was saturated samples. Testing the research hypothesis using SPSS 22 for Windows. The results showed that motivation has a positive and significant effect on employee performance, which means that when employees have a high responsibility for their work, it will be increased by an increase in employee performance. Compensation has a positive and significant effect on employee performance, which means that the better the facilities received by the employee will be followed by an increase in performance. Work conflict has a positive and significant effect on employee performance, which indicates that fewer communication errors made by employees will increase employee performance. Based on these results, to optimize employee performance, policies or regulations are needed to maximize motivation, compensation and work conflicts. Based on the direct experience of researchers in the data collection process, the information provided by respondents through questionnaires sometimes does not show actual opinions.